PERTIMBANGAN HAKIM DALAM MENJATUHKAN PIDANA PENJARA TERHADAP PELAKU TINDAK PIDANA PENCURIAN DI PENGADILAN NEGERI KELAS 1 A PADANG (Studi Putusan Nomor: 540/Pid.B/2020/PN Pdg) - Nurlinda Yenti, Gema Jaya Mardika dan (Normative Jurnal Ilmiah Hukum, 2021)
Judge's Consideration in Imposing Imprisonment Against Perpetrators of the Crime of Theft in Class 1 A Padang District Court In Decision Number: 540/Pid.B/2020/PN The defendant was charged with theft in aggravating circumstances, carried out by means of juridical and non-juridical considerations proving the defendant guilty imposed on Article 363 paragraph (1) 3rd, 5th of the Criminal Code and Law Number 8 of 1981 concerning the Criminal Procedure Code and other relevant laws and regulations, so that the defendant is sentenced to imprisonment for 1 (one) year and 6 (six) months is deducted while the defendants are in temporary detention. Evidence in the perpetrators of the crime of theft at the Class 1 A Padang District Court In Decision Number: 540/Pid.B/2020/PN Pdg, considering the elements a) whoever, b) taking something that wholly or partly belongs to another person, c) with the intention of illegally possessing, d) at night in a residence or on a closed yard on which there is a residence, which is carried out by a person who is there without the knowledge or against the wishes of the entitled person, e) which is carried out by the wrongdoer by entering the crime scene in order to be able to reach the goods to be taken, by dismantling, breaking, or climbing or by using false keys, false orders or false official clothes.